2023
DOI: 10.2196/43780
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of a Messenger-Based Psychosocial Chat Counseling Service on Further Help-Seeking Among Children and Young Adults: Longitudinal Study

Abstract: Background Mental crises have high prevalences in adolescence. Early interventions appear to be highly important to diminish the risk of the deterioration, recurrence, or chronification of symptoms. In recent years, various providers have started offering live chat support in psychological crises. The messenger-based psychological counseling service krisenchat aims to support young people in crises and, if necessary, provide a recommendation for a referral to the health care system or to seek furth… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 47 publications
(70 reference statements)
0
3
0
Order By: Relevance
“…We applied a time based train-test split and used the 14,931 chatters that received a consultation before September 2022 as train set and saved the newest 3,942 chatters (21%, consultation between September 2022 and December 2022) for a one-time final evaluation of the algorithm’s performance. As reported elsewhere 14 , those contacting krisenchat are mostly female and aged on average around 17, with psychiatric symptoms as the most likely reason for contacting the service. On average, the first consultation of chatters consisted of 25.4 messages of the chatter (SD = 20.8) and 17.7 by the counselor (SD = 12.1).…”
Section: Methodsmentioning
confidence: 54%
See 1 more Smart Citation
“…We applied a time based train-test split and used the 14,931 chatters that received a consultation before September 2022 as train set and saved the newest 3,942 chatters (21%, consultation between September 2022 and December 2022) for a one-time final evaluation of the algorithm’s performance. As reported elsewhere 14 , those contacting krisenchat are mostly female and aged on average around 17, with psychiatric symptoms as the most likely reason for contacting the service. On average, the first consultation of chatters consisted of 25.4 messages of the chatter (SD = 20.8) and 17.7 by the counselor (SD = 12.1).…”
Section: Methodsmentioning
confidence: 54%
“…First, studies have shown that chat-based synchronous interventions can be an effective treatment and prevention method for children and young adults with diverse mental health symptoms 10 12 . Additionally, those hotlines proved to be a first contact point for the youth 13 , serving as access points into further mental health treatment 14 . Therefore, besides the provision of efficient counseling during the chat interaction, the identification of those in need of additional help and their redirection towards appropriate care is a key task of those hotlines.…”
Section: Introductionmentioning
confidence: 99%
“…First studies have shown that chat-based synchronous interventions can be an effective treatment and prevention method for children and young adults with diverse mental health symptoms 10,11,12 . Additionally, those hotlines proved to be a first contact point for the youth 13 , serving as access points into further mental health treatment 14 . Therefore, besides the provision of efficient counseling during the chat interaction, the identification of those in need of additional help and their redirection towards appropriate care is a key task of those hotlines.…”
Section: Introductionmentioning
confidence: 99%